2022
DOI: 10.7759/cureus.23167
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Duodenal Diverticulitis: A Case Report of a Rare Surgical Entity Treated by Roux-en-Y Deriving Intestinal Patch

Abstract: Perforated diverticulitis is a rare but serious complication associated with a significant mortality rate. Although many cases of conservative treatment have been reported, surgery remains the mainstay for perforated duodenal diverticulitis.We report a rare case of a 55-year-old female who presented with epigastric pain without fever. Computed tomography revealed a 3 cm perforated duodenal diverticulum of the D2 part of the duodenum with a localized abscess. After the failure of conservative treatment, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…If the symptoms of DDP do not improve after 24 h, surgery may become necessary. Evangelos et al reported a recurrence of perforation on day 15 after the onset despite follow-up CT on day 4 of hospitalization showing no indications of a possible relapse ( 8 ). Kapp et al reported that surgery setup required 48 to 72 h ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…If the symptoms of DDP do not improve after 24 h, surgery may become necessary. Evangelos et al reported a recurrence of perforation on day 15 after the onset despite follow-up CT on day 4 of hospitalization showing no indications of a possible relapse ( 8 ). Kapp et al reported that surgery setup required 48 to 72 h ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to DPS, it is noteworthy to mention Pierre Marie-Bamberger syndrome (PMBS), which can accompany some patients with SFTs [ 28 ]. PMBS, also known as clubbing-osteogenic hypertrophy of the ends of the fingers, is characterised by the enlargement of the fingertips, clubbing of the fingers, and hypertrophic osteoarthropathy [ 28 , 29 ]. While not exclusive to SFTs, PMBS has been reported in association with SFTs, particularly those located in the pleura.…”
Section: Clinical Features Of Doege-potter Syndromementioning
confidence: 99%
“…The exact mechanisms underlying the development of Pierre PMBS in the context of SFTs remain incompletely understood, but it is believed to be related to the release of various growth factors and cytokines by the tumour. Recognition of PMBS in patients with SFTs is important for comprehensive clinical assessment and management [ 29 , 30 ].…”
Section: Clinical Features Of Doege-potter Syndromementioning
confidence: 99%